(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The security of video applications such as commercial videos, military videos and others have become an important field of research recently. One of the most secure algorithms is Advanced Encryption Standard (AES) algorithm;however this algorithm is inefficient for dealing with video encryption due to its slowness property. This paper proposes a new modified of AES to make it more suitable for encrypting digital video. The Modification focuses on the slowest transformations in original AES which is mix columns transformations and replace them with new Henon map chaotic based mask and one mix columns transformation. Resulting in a significant reduction in encryption and decryption time and enhance the security level of AES algorithm, and also the key space is increased as observed in the simulation results of proposed system.